Effects of Area of Walls, Internal Corridors, and Stairs on the Built-Up Area of Houses - Hassan Faisal Jaafar; abdulbaqi Ghazi; Ali I. Sabur; Mustafa Özakça (Journal of Engineering and Sustainable Development)
Designing a house requires developing initial perceptions of many elements’ spaces, which consume quite a bit of space and are often neglected, including the space of stairs, internal corridors, and walls. Through a survey of previous literature related to the subject, it became clear that there is no concept or study concerned with determining the approximate proportions of the wall area and the staircase area with the internal corridors inside the residential house and the extent of their impact on the remaining spaces The deductive method for analyzing a group of samples to reach an approximate unified result resulting in approximately 17% for the combined area of stairs and internal corridors, and 17% for walls. Accordingly, a preliminary conception of the area of the remaining spaces in the residential house can be developed. Considering such a percentage in the architectural designer will reduce the differences between the architect and the client and give an initial visualization of possible spaces.